2022
DOI: 10.3390/molecules27154858
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Photon Fluorescent Probe for the Visual Detection of Peroxynitrite in Living Cells and Zebrafish

Abstract: Peroxynitrite (ONOO−), as an important reactive oxygen species (ROS), holds great potential to react with a variety of biologically active substances, leading to the occurrence of various diseases such as cancer and neurodegenerative diseases. In this work, we developed a novel mitochondria-localized fluorescent probe, HDBT-ONOO−, which was designed as a mitochondria-targeting two-photon fluorescence probe based on 1,8-naphthylimide fluorophore and the reactive group of 4-(bromomethyl)-benzene boronic acid pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Peroxynitrite (ONOO À ) is an active oxygen species, which is produced endogenous by the combination of nitric oxide and superoxide anion radical, and is associated with a variety of physiological and pathological activities. [80,81] As a strong oxidant, ONOO À can react with proteins, lipids, biological mercaptans and other substances, and its own accumulation can also cause the enhancement of cellular oxidative stress damage. As shown in Figure 4B, Zhang et al reported a C=C bond based fluorescent probe named Mito-WQPhOH for the detection of ONOO À in mitochondria.…”
Section: Onoo à Detectionmentioning
confidence: 99%
“…Peroxynitrite (ONOO À ) is an active oxygen species, which is produced endogenous by the combination of nitric oxide and superoxide anion radical, and is associated with a variety of physiological and pathological activities. [80,81] As a strong oxidant, ONOO À can react with proteins, lipids, biological mercaptans and other substances, and its own accumulation can also cause the enhancement of cellular oxidative stress damage. As shown in Figure 4B, Zhang et al reported a C=C bond based fluorescent probe named Mito-WQPhOH for the detection of ONOO À in mitochondria.…”
Section: Onoo à Detectionmentioning
confidence: 99%
“…There are many reports where borate was used as the recognition unit for H 2 O 2 , but peroxynitrite is more efficient in reacting with borate . Although some reports are based on the borate reaction of peroxynitrite, the product converts to its parent alcohols after the reaction. , To our best knowledge, there is only one report where borate converted to a pyridynile-based product after a reaction with peroxynitrite . Therefore, we have also designed a borate recognition-based probe in which a pyridinyl product is formed upon reaction with peroxynitrite.…”
Section: Introductionmentioning
confidence: 99%